Growth performance of African catfish (Clarias sp.) juvenile fed on the diets containing various chromium content - Aryansyah, H.; Mokoginta, I.; Jusadi, D. (Jurnal Akuakultur Indonesia, 2007)
This experiment was conducted to determine the effect of different dietary chromium level on the growth performance of catfish (Clarias sp.) juvenile. Five experimental diets contain different chromium level, namely diet A (as a control diet) 0.01; B 1.30; C 2.60; D 3.90 and E 5.20 mg/kg diet were used in this experiment. Fish with body weight of  5.57 ± 0.01 g/ind, fed on the experimental diet, twice a day, at satiation. Feeding trial was conducted for 60 days. Based on the evaluation of protein level of the whole body, protein and lipid retention, daily growth rate and feed efficiency, it was concluded that the optimum dietary chromium level for catfish  juvenile was 2.60 mg/kg diet. Keywords: chromium, growth, Clarias sp.   ABSTRAK Penelitian ini dilakukan untuk mengetahui pengaruh pemberian kromium dengan level berbeda terhadap pertumbuhan ikan lele (Clarias sp.) juvenil.  Lima jenis pakan yang mengandung kromium berbeda, yaitu pakan A  (kontrol) 0,01; B 1,30; C 2,60; D 3,90 dan pakan E 5,20 mg/kg digunakan dalam penelitian ini. Ikan dengan bobot 5,57 ± 0,01 g/ind., diberi pakan 2 kali sehari secara satiasi.  Pemeliharaan ikan dilakukan selama 60 hari.  Berdasarkan analisa retensi protein, kandungan protein dan retensi lemak dalam tubuh ikan lele, disimpulkan bahwa kadar kromium yang optimum untuk juvenil ikan lele adalah 2,60 mg/kg pakan. Kata kunci: kromium, pertumbuhan, Clarias sp.